2021
DOI: 10.1088/1741-4326/ac24d3
|View full text |Cite
|
Sign up to set email alerts
|

Design and integration studies of a diagnostics slim cassette concept for DEMO

Abstract: The diagnostics slim cassette (DSC) is a concept currently proposed for DEMO to host the microwave reflectometry diagnostic in a dedicated poloidal section, for the feedback control of plasma position and shape, also providing the radial edge density profile at several poloidal angles. This DSC, which is expected to house up to 100 antennas and waveguides, is to be integrated with the breeding blanket (BB) segments. Moreover, it is being designed with remote handling compatibility in mind to facilitate a ‘fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results showed that close to the equatorial plane, a single pair of antennas can provide good spatial resolution. In regions of higher plasma curvature, however, clusters of 3-5 antennas (1 for emission and 2-4 for reception) may be needed to fully capture the reflected waves [32,33]. Considering measurements in 16 gaps on a poloidal plane around the plasma, up to 80 antennas might be required to fulfil the measurement requirements.…”
Section: Microwave Reflectometry As a Plasma Position Diagnostic For ...mentioning
confidence: 99%
“…The results showed that close to the equatorial plane, a single pair of antennas can provide good spatial resolution. In regions of higher plasma curvature, however, clusters of 3-5 antennas (1 for emission and 2-4 for reception) may be needed to fully capture the reflected waves [32,33]. Considering measurements in 16 gaps on a poloidal plane around the plasma, up to 80 antennas might be required to fulfil the measurement requirements.…”
Section: Microwave Reflectometry As a Plasma Position Diagnostic For ...mentioning
confidence: 99%
“…Using Paraview, the values for each of these quantities were obtained at the 60 The model of the DSC is presented in Figures 7 and 8, integrated in the reference model of Figure 2. As described in more detail in [16], the DSC has a thickness of 25 cm in the toroidal direction and the same poloidal shape as the blankets, ~12 m in height and approximately 52 tons in weight (similar density to the WCLL blankets). A homogenized mixture of EUROFER and water was assumed for the DSC, with volume fractions of 83.6% and 16.4%, respectively, representative of a small module with a cooling system studied in a previous work [24].…”
Section: Mcnp Modelsmentioning
confidence: 99%
“…These include spectroscopy diagnostics [7], neutron/gamma cameras [8,9], radiated power and soft Xray intensity [10] and IR polarimetry/interferometry [11], with the eventual addition of collective Thomson scattering [12], still under study. For diagnostics that require access to the plasma from several poloidal positions, such as MW reflectometry [13] and ECE [14], the diagnostics slim cassette (DSC) concept has been developed [15][16][17] as a modular approach compatible with the remote handling operations of the breeding blanket (BB). Thermocurrent measurements are planned to be integrated within the divertor cassette [18], while Faraday sensors are distributed poloidally on the outer surface of the vacuum vessel (VV) [19].…”
Section: Introductionmentioning
confidence: 99%